2013
DOI: 10.1093/jxb/ert108
|View full text |Cite
|
Sign up to set email alerts
|

Banana ethylene response factors are involved in fruit ripening through their interactions with ethylene biosynthesis genes

Abstract: The involvement of ethylene response factor (ERF) transcription factor (TF) in the transcriptional regulation of ethylene biosynthesis genes during fruit ripening remains largely unclear. In this study, 15 ERF genes, designated as MaERF1–MaERF15, were isolated and characterized from banana fruit. These MaERFs were classified into seven of the 12 known ERF families. Subcellular localization showed that MaERF proteins of five different subfamilies preferentially localized to the nucleus. The 15 MaERF genes displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(127 citation statements)
references
References 53 publications
5
119
0
Order By: Relevance
“…Tournier et al (2003) demonstrated that SlERF2, an ERF that binds a GCC-box, plays an important role during the ripening of tomato. Similar patterns were observed for ERFs expressed during the ripening of different fruits (Xiao et al, 2013). The overexpression of LeERF1 shortens the fruit postharvest life (Li et al, 2007), while LeERF2 modulates ethylene biosynthesis in tomato and tobacco.…”
Section: Discussionsupporting
confidence: 69%
“…Tournier et al (2003) demonstrated that SlERF2, an ERF that binds a GCC-box, plays an important role during the ripening of tomato. Similar patterns were observed for ERFs expressed during the ripening of different fruits (Xiao et al, 2013). The overexpression of LeERF1 shortens the fruit postharvest life (Li et al, 2007), while LeERF2 modulates ethylene biosynthesis in tomato and tobacco.…”
Section: Discussionsupporting
confidence: 69%
“…S1). Furthermore, we also demonstrated that GST-MaERF11-N proteins could bind to the regions including the GCC-box in the promoters of MaEXP2, MaEXP7, and MaEXP8, as well as an ethylene biosynthetic gene MaACO1, which has been identified in our previous study (Xiao et al, 2013; Fig. 2D; Supplemental Fig.…”
Section: Maerf11 Has Transcriptional Repression Activitysupporting
confidence: 75%
“…In a previous study, sequence analysis displayed that MaERF11 includes the EAR motif, a repression domain, implying that MaERF11 might act as a transcriptional repressor (Xiao et al, 2013). To examine whether MaERF11 possesses transcriptional repression activity, the VP16 transcriptional activation domain was used as a positive control and the full-length cDNA of MaERF11 fused with VP16 was used as an effector, and the respective constructs were expressed in tobacco (Nicotiana tabacum cv Bright Yellow 2) BY2 protoplasts (Fig.…”
Section: Maerf11 Has Transcriptional Repression Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Banana ripening is an irreversible process, characterized by a climacteric respiratory pattern, which is stimulated by an autocatalytic production of ethylene and physiological and metabolic changes that are sensitive to temperature and ethylene itself (XIAO et al, 2013). Several studies have been conducted on control postharvest banana quality, discussing storage conditions and treatments to prolong its shelf life (FERNANDES et al, 2010;WANG et al, 2014;ZHANG et al, 2010).…”
Section: Introductionmentioning
confidence: 99%